1992
DOI: 10.1002/app.1992.070440813
|View full text |Cite
|
Sign up to set email alerts
|

Study of cryostructurization of polymer systems. IX. Poly(vinyl alcohol) cryogels filled with particles of crosslinked dextran gel

Abstract: SYNOPSISThe influence of deformable disperse filler on rheological and thermal properties of poly (vinyl alcohol) cryogels (obtained by freezing-thawing of concentrated aqueous solutions of the polymer) was studied. Spherical particles of crosslinked dextran gel-the Sephadex beads of two types: G-25 and G-100-were used as filler. It was found that an increase in the filler concentration from 0 to 20 wt % produced an increase in the composite cryogel strength; the greater reinforcement effect was observed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 28 publications
(5 reference statements)
0
22
0
Order By: Relevance
“…In the previous research, where the EFE was used in respect to cryoPVAGs, the same "inadvertent" assumption (certainly, without the knowledge on the sol/gel-fraction ratio) was also made. 29,45 But the data of the present work evidently demonstrated that only a definite portion of the initial amount of PVA macromolecules was involved in the structure of gel framework of macroporous cryogels, and consequently, only these "gel-inserted" chains should be responsible for the values of fusion enthalpies found in the experiments.…”
Section: On the Thermophysical Parameters Of The Polymer Network In Pmentioning
confidence: 69%
See 1 more Smart Citation
“…In the previous research, where the EFE was used in respect to cryoPVAGs, the same "inadvertent" assumption (certainly, without the knowledge on the sol/gel-fraction ratio) was also made. 29,45 But the data of the present work evidently demonstrated that only a definite portion of the initial amount of PVA macromolecules was involved in the structure of gel framework of macroporous cryogels, and consequently, only these "gel-inserted" chains should be responsible for the values of fusion enthalpies found in the experiments.…”
Section: On the Thermophysical Parameters Of The Polymer Network In Pmentioning
confidence: 69%
“…Thus, earlier it was shown 29,44,45 that for the determination of fusion enthalpies of PVA cryogels formed under various freezing-thawing conditions, a well-known approach based on the Eldridge-Ferry equation (EFE) [lnC ϭ (⌬H/RT f ) ϩ const.] 46 could be used, implying the measurements of gel-fusion temperatures depending on the polymer concentration in the samples.…”
Section: On the Thermophysical Parameters Of The Polymer Network In Pmentioning
confidence: 99%
“…The thawed-out samples usually presented as opaque gels (cryoPVAGs), in which rheological properties were evaluated by the penetration method 15 essentially in accordance with the procedure used in our previous research for the investigation of various PVA cryogels (for details see refs. 10,12,16 ) using the modified Kargin-Sogolova dynamometric balance. 17 The measurements were done at 22 Ϯ 1°C, the load was 4.9 mN, the punch had a spherical top 5 mm in diameter.…”
Section: Methodsmentioning
confidence: 99%
“…10 However after 15 min, the microwave energy causes a breakdown of the chain bond, creates a new pathway to solvent diffusion and leads to a decrease of carrier mobility between the conductive aggregates. 11 Indeed, the lower value of the electrical conductance at 20 min exposure to microwaves con®rms that microwaves cause degradation in the rubber matrix (foam-like).…”
Section: Separation Distance Between Conductive Aggregatesmentioning
confidence: 97%